2004
DOI: 10.1073/pnas.0307345101
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localization and molecular partners of BIG1, a brefeldin A-inhibited guanine nucleotide-exchange protein for ADP-ribosylation factors

Abstract: Brefeldin A-inhibited guanine nucleotide-exchange protein 1 (BIG1) is an Ϸ200-kDa brefeldin A-inhibited guanine nucleotideexchange protein that preferentially activates ADP-ribosylation factor 1 (ARF1) and ARF3. BIG1 was found in cytosol in a multiprotein complex with a similar ARF-activating protein, BIG2, which is also an A kinase-anchoring protein. In HepG2 cells growing with serum, BIG1 was primarily cytosolic and Golgi-associated. After incubation overnight without serum, a large fraction of endogenous BI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 30 publications
1
29
0
1
Order By: Relevance
“…Nucleoli were isolated from 293T cells according to the method of Padilla et al (2004), with slight modifications. 293T cells were harvested and washed three times with 1 ml of ice-cold PBS, suspended in 20 ml of RSB buffer (10 mM Tris⅐HCl, pH 7.5/10 mM NaCl/1.5 mM MgCl 2 ), incubated on ice for 30 min, and centrifuged at 500 ϫ g for 5 min at 4°C.…”
Section: Purification Of Nucleolimentioning
confidence: 99%
“…Nucleoli were isolated from 293T cells according to the method of Padilla et al (2004), with slight modifications. 293T cells were harvested and washed three times with 1 ml of ice-cold PBS, suspended in 20 ml of RSB buffer (10 mM Tris⅐HCl, pH 7.5/10 mM NaCl/1.5 mM MgCl 2 ), incubated on ice for 30 min, and centrifuged at 500 ϫ g for 5 min at 4°C.…”
Section: Purification Of Nucleolimentioning
confidence: 99%
“…Boal and Stephens also reported that Golgi structure was altered after BIG1 depletion (19). In addition to its Golgi association, BIG1 was accumulated in nuclei of serum-deprived HepG2 cells (20) or after their incubation with the immunosuppressive FK506 (21) or 8-Br-cAMP (22). In other conditions, BIG2 was associated with the trans-Golgi network and recycling endosomes (17,23).…”
mentioning
confidence: 94%
“…BIG1 had been localized at trans-Golgi structures (4,5); by electron microscopy, Golgi membranes in BIG1-depleted cells were less sharply defined and had more vesicle-like structures at the trans face than those in control or BIG2 siRNA-treated cells (6). BIG1 also was found in nuclei of serum-deprived HepG2 cells or after their brief incubation with the immunosuppressive drug FK506 (7) or with cAMP (8).…”
mentioning
confidence: 97%